Systematic literature review on the recent three-year trend mathematical representation ability in scopus database - Rizki Wahyu Yunian Putra; Sunyono Sunyono; Een Yayah Haenilah; Hasan Hariri; Sugeng Sutiarso; Nurhanurawati Nurhanurawati; Nanang Supriadi (Jurnal Infinity, 2023)
Mathematical representation is essential as the gateway to mastering mathematical literacy. This literature study aims to determine the growth of students' mathematical representation abilities in the last three years. This literature study presents a literature review on the development of mathematical representations, including media, strategies, and measurement instruments to serve as the basis for future mathematical representations. The literature study method used is the SLR (Systematic Literature Review), utilizing a review procedure that refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework in the period 2020 to 2022 because the growth in literature studies on mathematical representations is very significant and latest. Data were collected by reviewing 24 Scopus-indexed articles and proceedings from the Scopus database. The study's results reveal that from the 24 selected literature, it can be interpreted if the mathematical representation ability can be improved and fulfills the indicators of mathematical representation itself by providing innovation in media, strategies, and instruments in learning mathematics. The innovations provided can be in the form of technology integration (Geogebra), no longer conventional strategies (RME strategy), and instrument indicators of the representation itself. Thus the ability of students' mathematical representations is no longer included in the low category in solving mathematical problems.